2002
DOI: 10.1002/j.2161-1920.2002.tb00844.x
|View full text |Cite
|
Sign up to set email alerts
|

web‐assisted vocational test interpretation

Abstract: Despite the increasing availability of online counseling services, many questions remain unanswered. This study compared the effectiveness of a specific employment counseling activity, vocational interest inventory interpretation, across 3 delivery modalities: (a) online text chat; (b) online text chat with video cues; and (c) traditional, face-to-face interpretation. The difference in ratings of session value between text chat with video and face-to-face modalities was not significant; both were rated signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The study also noted that counselors who engage in online counseling might require specific training so that they can adapt their counseling skills to cyberspace . In a study that involved vocational test interpretation, Jones et al . (2002) found that clients reported no difference in session depth between face-to-face and videoconferencing interactions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also noted that counselors who engage in online counseling might require specific training so that they can adapt their counseling skills to cyberspace . In a study that involved vocational test interpretation, Jones et al . (2002) found that clients reported no difference in session depth between face-to-face and videoconferencing interactions .…”
Section: Discussionmentioning
confidence: 99%
“…Its presence is evident from computer-aided guidance systems (Harris-Bowlsbey & Sampson, 2005;Zunker, 2006) to online job applications . Fueling this technological revolution is the development of the Internet (Jones, Harbach, Coker, & Staples, 2002;Kirk, 2000;Stevens & Lundberg, 1998;Zunker, 2006) . The increasing sophistication of the Internet facilitates the immediate and easy dissemination of career information (Pope, 2000;Stevens & Lundberg, 1998), even allowing for the online administration of career assessments such as the Strong Interest Inventory and the Self-Directed Search (O'Halloran, Fahr, & Keller, 2002) .…”
mentioning
confidence: 99%
“…Studies like those conducted by Glueckauf (2001), marziali and donahue (2006), and others (Wade et al, 2005a;2005b;2006a) demonstrate the potential efficacy of online or Web-based therapeutic models and support them as viable options for therapeutic processes (Sussman, 2000). These studies also underscore the potential utility of videoconferencing as an emerging tool for the delivery of online therapeutic care (Jones et al, 2002;mcFadden, 2000).…”
Section: Web-based Therapeutic Interventions: a Review Of The Literaturementioning
confidence: 94%
“…Thus far, only a handful of studies (Wade et al, 2006a;Wade, Wolfe, Brown, & Pestian, 2005a;2005b) have reported on the use and effectiveness of family therapy using SVC. However, there is supportive research suggesting clients receiving therapy via SVC have similar clinical improvements as clients receiving face-to-face office visits (Jones, Harbach, Coker, & Staples, 2002;marziali & donahue, 2006;mcFadden, 2000;Simpson et al, 2005;Sussman, 2000). Thus, Web-based therapeutic interventions have the potential to meet the needs of families by providing nontraditional access to therapeutic support in instances in which such support is limited or unavailable.…”
mentioning
confidence: 99%
“…The addition of video and chat software to the Internet has made possible a virtual in-person test interpretation without a physical, onsite meeting that is called web-based test interpretation. A groundbreaking, although admittedly exploratory, investigation of web-based test interpretation was undertaken by Jones, Harbach, Coker, and Staples (2002). Using Holland's (1985) Vocational Preference Inventory, they undertook test interpretation in three modes: face to face (the typical counseling methodology), chat (actually a set of e-mail exchanges), and chat-video (e-mail exchanges plus a webcam image).…”
Section: New Modes Of Test Interpretationmentioning
confidence: 99%